Water Vapor Blending Ratio Effects on Combustion Thermal Performance and Emission of Hydrogen Homogeneous Charge Compression Ignition - Wenhua Yuan; Xueliang Huang; Jun Fu; Yi Ma; Guangming Li; Qike Huang (Energies, 2022)
A numerical model of the micro-free-piston engine was developed and its correctness was verified by the comparison between the simulation and referential experiment results under the same work conditions. Based on this numerical model, the effects of the water vapor blending ratio (α) on combustion thermal performance and emission characteristics of hydrogen (H2) homogeneous charge compressing ignition (HCCI) were investigated numerically. The water vapor impact on combustion temperature was analyzed as well. The simulation results reveal that when the initial equivalent ratio is 0.5, blending H2 with water vapor can delay the ignition time and prolong the whole process. At the same time, the addition of water vapor to H2 decreases the peak combustion temperature and pressure, which will alleviate the detonation phenomenon of the combustion chamber. Moreover, the power output capacity and NOx emissions decrease with the increase in α. When α increases to 0.8, the mixture gas cannot be compressed to ignite. Finally, the dilution effect, thermal effect, and chemical effect of water vapor all have the potential to lower the combustion temperature and the dilution effect plays the leading role.